THE EFFECT OF CLUSTERING TECHNIQUE UPON STUDENTS' ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH OF THE TENTH GRADE STUDENTS OF SMA N 3 SINGARAJA IN THE ACADEMIC YEAR 2013/2014 - ., I Gede Pratama Danan Jaya; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Kadek Sonia Piscayanti, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study was conducted to find out the effect of clustering technique on students’ achievement in writing descriptive paragraph. The population was the tenth grade students in SMA N 3 Singaraja which was consisted of 320 students. Cluster random sampling was used to choose the experimental group and control group. The design of this study was a Posttest-Only Control Group Design. The result of the treatment was identified through post-test which was given at the end of the treatment to see the significant difference between the experimental groups who had been treated using clustering technique and the control group who had been treated using the conventional teaching technique. The findings of the study showed that the mean score for experimental group was 79.45 and the mean score for the control group was 71.80. The result of t-test reveals that t¬obs 6.292 was higher than the value of tcv at 2.58 at level significance 0.01. This means that the null hypothesis is rejected. Thus, it can be concluded that there is a significant difference in students’ achievement in writing descriptive paragraph between the students who were taught by using clustering technique and those who were taught by using conventional teaching techniqueKata Kunci : writing achievement, clustering technique, descriptive paragraph This study was conducted to find out the effect of clustering technique on students’ achievement in writing descriptive paragraph. The population was the tenth grade students in SMA N 3 Singaraja which was consisted of 320 students. Cluster random sampling was used to choose the experimental group and control group. The design of this study was a Posttest-Only Control Group Design. The result of the treatment was identified through post-test which was given at the end of the treatment to see the significant difference between the experimental groups who had been treated using clustering technique and the control group who had been treated using the conventional teaching technique. The findings of the study showed that the mean score for experimental group was 79.45 and the mean score for the control group was 71.80. The result of t-test reveals that t¬obs 6.292 was higher than the value of tcv at 2.58 at level significance 0.01. This means that the null hypothesis is rejected. Thus, it can be concluded that there is a significant difference in students’ achievement in writing descriptive paragraph between the students who were taught by using clustering technique and those who were taught by using conventional teaching techniquekeyword : writing achievement, clustering technique, descriptive paragraph